SCIATICA SECONDARY TO SCIATIC NERVE SCHWANNOMA – A RARE CASE REPORT - DR.DEEPAK CHAVAN,; DR.GIRISH KULLOLLI, (International Journal of Pharma and Bio Sciences, 2014)
Schwannomas are encapsulated and benign peripheral nerve sheath tumors. Their occurrence in extracranial locations is rare. Schwannomas most commonly occur in adults between 20 and 50 years of age. Their symptomatology usually mimics sciatic pain due to herniated disc. The most common clinical presentation of sciatic nerve schwannoma is a painful palpable mass. A 25-year female patient was admitted to our neurosurgery department with a slow-growing mass in the medial right posterior thigh. Magnetic resonance imaging (MRI) showed a mass involving the right sciatic nerve in its middle portion. No neurological deficit was noted postoperatively. The result of the histopathological examination was reported as a schwannoma. We report a case of large sciatic schwannoma with chronic sciatica.